Exposure to deltamethrin in adolescent mice induced thyroid dysfunction and behavioral disorders. (February 2020) - Zhang, Jingwen; Liu, Haoyue; Li, Jiangning; Lou, Lixiang; Zhang, Shaozhi; Feng, Daofu; Feng, Xizeng
Abstract: Deltamethrin (DM) has become one of the most widely used insecticides in the world due to its low toxicity, high efficiency and low persistence in soil. However, it is still unknown whether DM exposure has any effects on the Hypothalamic-Pituitary-Thyroid (HPT) axis in adolescent mice. In this study, the open field test and circadian activity test showed that DM exposure increased activity. There was no significant difference between the groups in the light/dark box test and nest building test. Forced swimming test showed that after 6 and 12 mg kg −1 DM exposure 28 days, the immobility time was increased and the swimming time was reduced. After 6 mg kg −1 DM treatment, the thyroid stimulating hormone (TSH) content increased, and thyrotropin releasing hormone (TRH), triiodothyronine (T3) and thyroxine (T4) decreased. After exposure to 6 and 12 mg kg −1 DM, mRNA levels of HPT axis-related genes were destroyed. The histological examination showed that, the DM groups mice thyroid tissues appeared expanded thyroid follicles, scanty colloid and hyperplastic thyroid cells. Western blot results showed that the expression level of tyrosine hydroxylase (TH) protein decreased and the content of dopamine transporter (DAT) protein increased in DM treated mice striatum. Collectively, our results indicated that DM exposure could induce thyroid dysfunction and behavioral disorders in adolescent mice. Highlights: Adolescent DM exposure increased activities, particularly at night. Mice exposed to DM may exhibit depression-like behavior. DM exposure caused disturbance in the hormones and the expression of related genes. DM exposure influenced protein expression of DAT and TH in the striatum.